Water degrading effects on the bond behavior in FRP-strengthened masonry - Ghiassi, Bahman (2013)
Fiber reinforced polymers are being extensively used for external strengthening of masonry structures. However, durability of this strengthening technique under environmental conditions is still under inves- tigation. Previous studies indicate that moisture plays an important role in the durability of bond between FRP and substrate. Moisture can cause degradation in the bond behavior and also in the mechan- ical properties of the constituent materials. This paper presents and discusses the results of an experi- mental investigation on the effects of moisture on the bond behavior in FRP-strengthened masonry bricks. The degradation in the bond performance has been investigated by performing pull-off and pull-out tests on the conditioned specimens. The change in the mechanical properties of the materials has also been investigated. Comparative analysis has been performed and the results are presented and critically discussed.